Effect of resistance training on bioelectrical phase angle in older adults: a systematic review with Meta-analysis of randomized controlled trials - Campa, Francesco; Colognesi, Lucas Antonio [UNESP]; Moro, Tatiana; Paoli, Antonio; Casolo, Andrea; Santos, Leandro; Correia, Rafael Ribeiro [UNESP]; Lemes, Ítalo Ribeiro [UNESP]; Milanez, Vinícius Flávio; Christofaro, Diego Destro [UNESP]; Cyrino, Edilson Serpeloni; Gobbo, Luís Alberto [UNESP] (Springer Nature, 2022)
Resistance training has been proposed as a valid practice to counteract the aging effect on body mass and its components, which can be easily evaluated though the bioelectrical impedance analysis. This study aimed to achieve a systematic review with meta-analysis on the impact of resistance training on bioelectrical proprieties in older adults. A literature review was done in four electronic databases up to 1 January 2022. The inclusion criteria were: (i) participants aged ≥ 60 years; (ii) resistance training lasted ≥ 8 weeks; (iii) measurement of raw bioelectrical parameters in randomized controlled study designs. The outcomes of the trial had to be bioelectrical phase angle (PhA), resistance (R), and reactance (Xc). The methodological quality was assessed using the Rosendal scale. Overall, seven studies with a total of 344 participants were eligible for the analysis. The quality assessment yielded a score of 71.3%. Bioelectrical PhA (0.52 degree [95%CI 0.32, 0.71], p < 0.001) and Xc (3.58 ohms [95%CI 1.97, 5.19], p < 0.001) increased, whereas R decreased (-28.50 ohms [95%CI -41.39, -15.60], p < 0.001) after the resistance training programs. In this meta-analysis, resistance training promoted increases of PhA, which result from an increase in Xc concomitant with a reduction in R. According to the bioimpedance vector analysis, resistance-trained people experienced a beneficial leftward vector displacement, whilst inactivity induced a rightward vector displacement within the R-Xc graph. In future, more sophisticated and rigorous studies that address specific criteria, methods and targeted designs are required to identify which equipment and protocols allow for an optimization of the resistance training effects. Registration code in PROSPERO: CRD42020168057.
Keywords: Aging; BIA; BIVA; Body composition; Phase angle; Strength